Coping Schemas and Their Impact on Burnout (Docentes 2.0 Journal, 2026)
Currently, we live in an environment characterized by multiple demands in the social, family, and work spheres. The work environment, in particular, has attracted increasing attention, given the recognized impact of psychological well-being on employee performance. This research aimed to analyze the relationship between coping strategies and the manifestation of burnout syndrome in organizational contexts. To this end, a qualitative approach was employed, framed within the interpretive paradigm, using the hermeneutic method, a narrative-thematic design, and a documentary-analytical, cross-sectional approach. The population consisted of scientific studies published between 2017 and 2024, obtained from the following databases: Google Scholar, SciELO, Dialnet, and Redalyc. The bibliographic review technique and a document analysis matrix were used to organize and systematize the information into thematic categories. The analysis was critical, qualitative, and systematic. The results revealed that avoidant coping is associated with higher levels of burnout, while adaptive strategies, such as problem-solving and social support, act as protective factors. The discussion highlighted the influence of gender, resilience, and the methodological quality of the studies on the findings. In conclusion, the importance of strengthening adaptive coping strategies to mitigate burnout in the workplace is emphasized. Ethical principles and academic integrity were respected throughout the research process.
Keywords: Coping; Psychological Well-being; Burnout; Chronic Stress; Avoidant Coping